2011
DOI: 10.1111/j.1758-2229.2011.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of nirK‐ and nirS‐carrying bacteria to denitrifying conditions in the anoxic rice field soil

Abstract: Denitrification occurs actively in rice field soils. In the present study, the responses of nirK and nirS denitrifier communities to nitrate addition in the anoxic rice soil were determined through molecular analyses of nitrite reductase genes nirK and nirS and 16S rRNA genes. Denitrification occurred rapidly when nitrate was added at the beginning of anoxic incubation (experiment I). The structure of nirK-type denitrifiers did not change; but their abundance as determined by quantitative (real-time) PCR incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 63 publications
4
16
0
Order By: Relevance
“…This agrees with what was observed by correlations in the original data set (Enwall et al 2010) and in other studies reporting either a significant and/or stronger correlation between denitrification activity and nirS abundance when compared to nirK (Philippot et al 2009, Graham et al 2010. It has been suggested that nirS-and nirK-type denitrifier communities occupy different ecological niches (e.g., Santoro et al 2006, Desnues et al 2007, Smith and Ogram 2008, Yuan et al 2012) and coexisting nirS and nirK communities are likely not under the same community assembly rules (Jones and Hallin 2010). In another experimental agricultural system, Hallin et al (2012) observed that denitrification process rates could be maintained over a range of temperatures and salinity levels and this functional operating range was expanded for bacterial communities that assembled under certain soil management practices and contained key genotypes.…”
Section: Discussionsupporting
confidence: 91%
“…This agrees with what was observed by correlations in the original data set (Enwall et al 2010) and in other studies reporting either a significant and/or stronger correlation between denitrification activity and nirS abundance when compared to nirK (Philippot et al 2009, Graham et al 2010. It has been suggested that nirS-and nirK-type denitrifier communities occupy different ecological niches (e.g., Santoro et al 2006, Desnues et al 2007, Smith and Ogram 2008, Yuan et al 2012) and coexisting nirS and nirK communities are likely not under the same community assembly rules (Jones and Hallin 2010). In another experimental agricultural system, Hallin et al (2012) observed that denitrification process rates could be maintained over a range of temperatures and salinity levels and this functional operating range was expanded for bacterial communities that assembled under certain soil management practices and contained key genotypes.…”
Section: Discussionsupporting
confidence: 91%
“…In general, NO 3 – fertilization increased denitrifier nirS population size (Fig. A), consistent with Kong and colleagues () and Yuan and colleagues (), most likely because of the greater availability of NO 3 – to serve as a terminal electron acceptor. Fertilization was also found to affect nirS ‐denitrifier community composition, manifesting as clear and consistent shifts on the PCoA diagram (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…The abundance of nirS decreased with distance from the inlet while the greatest nirK abundance occurred in the central region of the bioreactor. This agrees with previous studies suggesting that nirS and nirK type denitrifiers have different niche preferences (Jones and Hallin, 2010), which would explain why they would respond differently to changing environmental conditions, as reported by others (Desnues et al, 2007;Enwall et al, 2010;Santoro et al, 2006;Smith and Ogram, 2008;Yuan et al, 2012). Since NO 3 À concentrations decreased to below detection limits in the outlet during the second half of the operational period, nirS abundance may have reflected substrate availability.…”
Section: Discussionsupporting
confidence: 87%